Operational Communication: A paradigm for applied research into police call-handling - Garner, Mark; Johnson, Edward (International Journal of Speech, Language and the Law, 2006)
Call-handlers’ work is pivotal in the day-to-day functioning of the police. They have to interpret the call and assess it in the light of procedures and current demands on resources. They thus set the agenda and act as gate-keepers to police assistance, help to shape relationships with the public and indirectly influence policy through their patterns of call classification. Despite this, there has been limited linguistic interest in call-handling, although some studies, particularly using conversation analysis, have been published. A much more applied approach to call-handling research is needed, however. In this paper, we attempt to answer the question, what would such an approach consist of? We suggest that a useful paradigm is provided by operational communication (OC) research, which is driven and informed by both theoretical linguistic considerations and practical institutional requirements. An outline of the recursive methodology of OC research is provided, which incorporates descriptive-analytical, prescriptive and evaluative phases. The intention is to provide both a stimulus and a possible method for further research in this important field.